Effect of Empiric Anti–Mycobacterium tuberculosis Therapy on Survival Among Human Immunodeficiency Virus–Infected Adults Admitted With Sepsis to a Regional Referral Hospital in Uganda - Hazard, Riley H.; Kagina, Peninah; Kitayimbwa, Richard; Male, Keneth; McShane, Melissa; Mubiru, Dennis; Welikhe, Emma; Moore, Christopher C.; Abdallah, Amir (In Open Forum Infectious Diseases, 2019)
Background: Mycobacterium tuberculosis is the leading cause of bloodstream infection among human immunodeficiency virus (HIV)–infected patients with sepsis in sub-Saharan Africa and is associated with high mortality rates. Methods: We conducted a retrospective study of HIV-infected adults with sepsis at the Mbarara Regional Referral Hospital in Uganda to measure the proportion who received antituberculosis therapy and to determine the relationship between antituberculosis therapy and 28-day survival. Results: Of the 149 patients evaluated, 74 (50%) had severe sepsis and 48 (32%) died. Of the 55 patients (37%) who received antituberculosis therapy, 19 (35%) died, compared with 29 of 94 (31%) who did not receive such therapy (odds ratio, 1.34; 95% confidence interval [CI], .56–3.18; P = .64). The 28-day survival rates did not differ significantly between these 2 groups (log-rank test, P = .21). Among the 74 patients with severe sepsis, 9 of 26 (35%) who received antituberculosis therapy died, versus 23 of 48 (48%) who did not receive such therapy (odds ratio, 0.58; 95% CI, .21–1.52; P = .27). In patients with severe sepsis, antituberculosis therapy was associated with an improved 28-day survival rate (log-rank test P = .01), and with a reduced mortality rate in a Cox proportional hazards model (hazard ratio, 0.32; 95% CI, .13–.80; P = .03). Conclusions: Empiric antituberculosis therapy was associated with improved survival rates among patients with severe sepsis, but not among all patients with sepsis.
Keywords: Africa; Mycobacterium tuberculosis; Sepsis; Uganda